2018
DOI: 10.3897/mycokeys.33.24704
|View full text |Cite
|
Sign up to set email alerts
|

The Northeast Chinese species of Psathyrella (Agaricales, Psathyrellaceae)

Abstract: Twenty seven species of Psathyrella have been found in Northeast China. Amongst them, P. conica, P. jilinensis, P. mycenoides and P. subsingeri are described as new species, based on studying morphological characteristics and phylogenetic analyses. Detailed morphological descriptions, line drawings and photographs of the new species are presented. Phylogenetic analysis of the nuclear ribosomal internal transcribed spacer (ITS) region and an identification key to the 27 Psathyrella species occuring in Northeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…4). Indeed, the phylogenetic tree shows that our specimen falls into the “ candolleana ” clade, such a heterogeneous group, including taxa from different morphology, ecology and geographic provenance and, amongst them, the above-cited P.typhae (Battistin et al 2014, Örstadius et al 2015, Yan and Bau 2018).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…4). Indeed, the phylogenetic tree shows that our specimen falls into the “ candolleana ” clade, such a heterogeneous group, including taxa from different morphology, ecology and geographic provenance and, amongst them, the above-cited P.typhae (Battistin et al 2014, Örstadius et al 2015, Yan and Bau 2018).…”
Section: Resultsmentioning
confidence: 92%
“…Consensus sequences were generated from both forward and reverse primer reads in the BioEdit sequence alignment editor, version 7.2.5 (Hall 1999), then homology searches were performed at the National Centre for Biotechnology Information (NCBI) Web site using BLAST. This sequence was then compared with those of the Psathyrella species deposited in GenBank on which the phylogenetic analysis had recently been performed (Padamsee et al 2008, Battistin et al 2014, Örstadius et al 2015, Yan and Bau 2018). A total of 45 ITS sequences, including three Coprinellus spp.…”
Section: Methodsmentioning
confidence: 99%
“…Padamsee et al Smith 1972). Later, Nagy et al (2013), Moreno et al (2015), Yan & Bau (2018) and Voto et al (2019) demonstrated that this clade is well-supported, characterized by species with pale colored basidiomata with fibrillose veil, and lacking pleurocystidia Among morphologically close species that fall in the same clade, the European P. leucotephra is the most similar species. It also grows caespitosely in large clusters of 10 basidiomata, presents utriform to utriform-lageniform cheilocystidia, small hilar appendix and inconspicuous germ pore on basidiospores, pale colored pileus, and whitish sericeous-fibrillose stipe.…”
Section: Discussionmentioning
confidence: 95%
“…PCR was carried out using a 25 μl reaction mixture in a thermocycler (Perkin-Elmer, Applied Biosystems). PCR amplification program was as follows: 5 min at 95°C, followed by 15 rounds of 1 min at 95°C, 30 s at 65°C (lowered by 1°C per cycle) and 1 min at 72°C, followed by 20 rounds of 1 min at 95°C, 30 s at 50°C and 1 min at 72°C, with a final extension of 10 min at 72°C (Yan & Bau 2018). Bidirectional sequencing was carried out at TsingKe (China) using the same primer pairs as used for PCR.…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%